2010
DOI: 10.1002/em.20553
|View full text |Cite
|
Sign up to set email alerts
|

Reactive species and mitochondrial dysfunction: Mechanistic significance of 4‐hydroxynonenal

Abstract: Mitochondrial dysfunction is a global term used in the context of “unhealthy” mitochondria. In practical terms, mitochondria are extremely complex and highly adaptive in structure, chemical and enzymatic composition, subcellular distribution and functional interaction with other components of cells. Consequently, altered mitochondrial properties that are used in experimental studies as measures of mitochondrial dysfunction often provide little or no distinction between adaptive and maladaptive changes. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 81 publications
(91 reference statements)
2
77
0
1
Order By: Relevance
“…4-HNE is considered to be an oxidized secondary product of lipids including CL (Liu et al, 2011) and would reflect mitochondrial dysfunction (Roede and Jones, 2010). Because CL was increased approximately threefold in iPLA 2 ␤-KO mice and the distribution of 4-HNE was not correlated with increased PCs with Figure 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4-HNE is considered to be an oxidized secondary product of lipids including CL (Liu et al, 2011) and would reflect mitochondrial dysfunction (Roede and Jones, 2010). Because CL was increased approximately threefold in iPLA 2 ␤-KO mice and the distribution of 4-HNE was not correlated with increased PCs with Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the distribution of 4-HNE was inconsistent with that of PAS-positive granules, which were identical to abnormal mitochondria containing dense granules, and the distal parts of axons were positive for 4-HNE suggested that 4-HNE might be accumulated in the distal part of degenerated axons that lacked axonal flow for transport of PAS-positive granules and that 4-HNE might not be massively produced until the mitochondrial double membranes had been disrupted. The presence of 4-HNE in axons might also aggravate axonal degeneration by attacking targets within the cell and expanding into the extracellular space (Roede and Jones, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…ALDH2*2 and disease unrelated to alcohol consumption: Ischemia occurs when blood flow to a certain tissue system is decreased, which can ultimately damage the tissue. In myocardial ischemia, most of the cardiac damage that occurs is believed to be due to excessive generation of reactive oxygen species, leading to peroxidation of unsaturated fatty acids that can form toxic end products such as the reactive aldehyde, 4-hydroxynonenal (4-HNE) [70,71]. Due to damage to the cardiac myocytes, excessive production of 4-HNE may ultimately impair cardiac contractility.…”
Section: Diseases Associated With the Inheritance Of Aldh2*2mentioning
confidence: 99%
“…Further, gamma-tocotrienol (GT3) also acts as a radioprotector for hematopoietic stem cells and progenitor cells in sub-lethally irradiated mice 37 . Mitochondria-targeted antioxidants would be important molecules providing protection from reactive oxygen species as mitochondria dysfunction by excess radicals can lead to cell death 39,40 . One such approach directed at the mitochondria in protecting cells from ionising radiation damage with Tempol 41 (Fig.…”
Section: Agents Modulate Thementioning
confidence: 99%